The Grit in the Oyster? Women's Parliamentary Organizations and the Substantive Representation of Women. (August 2019) - Allen, Peter; Childs, Sarah
This article addresses a foundational question of political representation: how do representatives act for those they represent? In a shift away from analyses of individual representatives' attitudes and behaviour, we identify Women's Parliamentary Organizations as potential critical sites and critical actors for women's substantive representation. Offering one of the most in-depth studies to date, our illustrative case is the long-standing UK Parliamentary Labour Party's Women's Committee. With a unique data set, and using both quantitative and qualitative methods, we systematically examine the Parliamentary Labour Party's Women's Committee efforts to substantively represent women over more than a decade. We find that the Committee sustains its focus on a small number of women's issues and interacts with party leadership to advance women's interests in a feminist direction. Our findings capture processes of political change, a frequently under-explored stage in studies of substantive representation. We close by identifying the potential for comparative research in this area.